The Development of Spatial Skills in Elementary School Students. Issue 2 (10th February 2017) - Carr, Martha; Alexeev, Natalia; Wang, Lu; Barned, Nicole; Horan, Erin; Reed, Adam
Abstract : Through five waves of data collection, this longitudinal study investigated the development of spatial skills in 304 elementary school children ( M age  = 7.64 years) as they progressed from the second to fourth grade. The study focused on whether multiple latent classes with different developmental profiles best explain development. Spatial skills were measured by tests featuring two‐dimensional figures. Mathematics achievement was measured by the statewide end‐of‐year test and was included as a distal outcome variable. The role of covariates, including socioeconomic status, verbal working memory, and gender, was also explored. The results indicate a need to view two‐dimensional spatial skills development as multidimensional with two developmental profiles predicted by socioeconomic status, verbal working memory, and gender. The developmental profiles predicted differences in mathematics achievement.